Market Power and Cartel Formation: Theory and an Empirical Test - Darren Filson; Edward Keen; Eric Fruits; Thomas E. Borcherding (Claremont McKenna College, Department of Economics, 2000)
Antitrust enforcement makes it difficult to test theories of cartel formation because most attempts to form cartels are blocked. However, federal laws allow U.S. produce growers to operate marketing cartels through devices called marketing orders. These cartels use quantity controls and quality standards to raise prices on fresh produce. Some growers have adopted marketing orders and others have not. This paper develops and tests a positive theory of the adoption of marketing orders. The theory suggests that growers in a region are more likely to adopt a marketing order if the demand for fresh produce is inelastic, the growers' market share in the fresh market is large, there are barriers to entry and expansion, the fraction of the output the growers ship to the fresh market is not too large or too small, growers are homogeneous, and large cooperatives exist. Probit analyses support these hypotheses.
Keywords: 330; marketing order; cartel; collusion; empirical; agriculture